Greene’s Hero: The Loss of the Religious Sense: The Impact of the First World War on English Literature (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In an essay Greene has lamented the loss of the religious sense in the English novel. “It was as if the world of fiction had lost a dimension,” he wrote. Greene is the leading exponent in English of the existentialist – psychological fiction which dominated European literature during the forties and afterwards. When Greene began his writing career, the period was marked by squalor, depression in moral, spiritual and religious values resulting from the First World War. The period can be well depicted in W.B. Yeat’s words when he sings sadly “Things fall apart, the centre cannot holdmere anarchy is loosened upon the world.” This disillusionment of the age resulted in a marked decline of the spiritual element, anxiety, apathy and agnosticism. Greene depicts in his works his modern mood of anxiety and boredom and man’s isolation in an alien universe. He protests against moral and spiritual degradation of man in our age. He repeatedly calls attention to the curious ‘malaise’ of modern man of considering the Church as old fashioned and out of date.